2007
DOI: 10.1016/j.proci.2006.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Detailed investigation of ignition by hot gas jets

Abstract: Experimental and numerical investigations of the ignition of hydrogen/air mixtures by jets of hot exhaust gases are reported. An experimental realisation of such an ignition process, where a jet of hot exhaust gas impinges through a narrow nozzle into a quiescent hydrogen/air mixture, possibly initiating ignition and combustion, is studied. High-speed laser-induced fluorescence (LIF) image sequences of the hydroxyl radical (OH) and laser Schlieren methods are used to gain information about the spatial and temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(51 citation statements)
references
References 11 publications
5
46
0
Order By: Relevance
“…These aspects include the problem of ignition by a hot inert gas stream, the dependence of flame speeds, positive or negative, on the flame curvature, and the stability of the stationary solutions encountered which have been called generalized flame balls. In particular, as Zeldovich flame balls are used as criteria for successful ignition in stagnant reactive gases, generalized flame balls have been shown to provide similar criteria for ignition by a hot radial stream, a step towards understanding ignition by more practical flows of hot gases such as jets [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These aspects include the problem of ignition by a hot inert gas stream, the dependence of flame speeds, positive or negative, on the flame curvature, and the stability of the stationary solutions encountered which have been called generalized flame balls. In particular, as Zeldovich flame balls are used as criteria for successful ignition in stagnant reactive gases, generalized flame balls have been shown to provide similar criteria for ignition by a hot radial stream, a step towards understanding ignition by more practical flows of hot gases such as jets [12].…”
Section: Discussionmentioning
confidence: 99%
“…at r = R. Here ψ * ≡ ψ(R − ), while h * ≡ h(R) and µ ≡ exp(h * /2) are given by (12) and (14), respectively.…”
Section: Stability Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In our case this is found to be ±8 %; this, in turn, corresponds to to an uncertainty of ±11 % in mixture fraction scale. Previous OH-LIF and numerical investigations conducted on the same experimental configuration have shown that ignition always occured at a region close to the jet tip along the axis rather than at the sides [2]. This can attributed to the disparate mixing behaviour as can be seen in Figure 1.…”
Section: Signal Evaluation Based On Reduced State Spacesmentioning
confidence: 81%
“…The combustion cell used for the NO-PLIF measurements is a simple and well-defined optically accessible constant-volume cell [2]. It consists of two vessels with the first vessel flanged to the second chamber.…”
Section: Methodsmentioning
confidence: 99%